The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.4187/respcare.04418
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Use of Nebulized Hypertonic Saline in Mechanically Ventilated Children: A Randomized Blinded Pilot Study

Abstract: -146.1] h) (P ‫؍‬ .03 by Wilcoxon rank-sum test). After adjusting for baseline levels of PEEP, the duration of mechanical ventilation did not differ between groups.Mechanical ventilation parameters, including dead space and dynamic compliance, did not differ between measurements taken before study drug administration versus measurements taken after. New onset wheezing following study drug administration was rare (1.0% with hypertonic saline vs 3.0% with placebo, P ‫؍‬ .36 by chi-square test). CONCLUSIONS: Admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 21 publications
1
6
0
1
Order By: Relevance
“…Although a small group of subjects may not allow generalization of findings, the possibility that those subjects could have been adversely affected by disconnection while receiving hypertonic saline cannot be ruled out. Despite some obvious limitations of the study by Shein et al 15 , their results are consistent with a few trials where nebulized hypertonic saline did not significantly improve any of the clinical outcomes measured. 14,18,19 The evidence supporting the prophylactic use of nebulized hypertonic saline for patients undergoing mechanical ventilation as a mucoactive agent and its impact on clinical outcomes is lacking.…”
Section: See the Original Study On Page 586supporting
confidence: 79%
See 2 more Smart Citations
“…Although a small group of subjects may not allow generalization of findings, the possibility that those subjects could have been adversely affected by disconnection while receiving hypertonic saline cannot be ruled out. Despite some obvious limitations of the study by Shein et al 15 , their results are consistent with a few trials where nebulized hypertonic saline did not significantly improve any of the clinical outcomes measured. 14,18,19 The evidence supporting the prophylactic use of nebulized hypertonic saline for patients undergoing mechanical ventilation as a mucoactive agent and its impact on clinical outcomes is lacking.…”
Section: See the Original Study On Page 586supporting
confidence: 79%
“…14,15,18 Nevertheless, the most recent meta-analysis evaluating the therapeutic and prophylactic nebulization of mucoactive agents in adult critically ill patients found very low quantity and quality of evidence to support their use. 14 Little evidence exists of their prophylactic use in the pediatric critical care setting to decrease the duration of mechanically ventilation, and no prospective blinded studies in children undergoing mechanical ventilation have been reported.…”
Section: See the Original Study On Page 586mentioning
confidence: 99%
See 1 more Smart Citation
“…A recent prospective study in intubated and mechanically ventilated children demonstrated no reduction in the duration of mechanical ventilation in a group who received 3% inhaled hypertonic saline compared with those who received normal saline aerosols. 99 Additionally, there was no improvement in lung mechanics or chest radiographic appearance following hypertonic saline administration, but 2 subjects had to be removed from the study because of hypoxemia that developed after hypertonic saline administration. Radioisotope studies of mucociliary clearance in healthy subjects treated with 3% inhaled hypertonic saline showed an initial acceleration of mucociliary clearance over the first 30 min after hypertonic saline inhalation but a slowing in mucociliary clearance at 3-6 h. 100 The authors speculated that the reduction in clearance was the result of depletion of mucus in the central airways.…”
Section: Medications That Alter Mucociliary or Cough Clearancementioning
confidence: 99%
“…However, in this non-blinded trial, no statistically significant differences in duration of mechanical ventilation, oxygen therapy or PICU stay between the groups were found. Similarly, Shein et al have focused on expectorants by studying routine nebulization with hypertonic (3%) saline versus normal (0.9%) saline in a pilot study [103]. With a very small sample size (n = 18), they found no differences between the groups for a number of outcomes, including duration of mechanical ventilation or chest Xray atelectasis score, as well as respiratory mechanics parameters before and after intervention.…”
Section: Pediatric Critical Care: Mechanically Ventilated Childrenmentioning
confidence: 99%